A Short Method for the Synthesis of Hydroxyoleic Acids. (9th December 2020) - Imperio, Daniela; Morelli, Laura; Panza, Luigi
Abstract: Enzymatic or microbiological oxidation of oleic acid can afford azelaic acid as a building block for bioplastics. However, during the oxidation, the formation of hydroxylated byproducts is observed. To better follow the oxidation reaction, the availability of reference compounds is of great importance. To this aim, the synthesis of a series of oleic acids hydroxylated at ω ‐ 1, ω ‐ 2, ω ‐ 3 positions is described without the use of protecting groups. The final products are obtained by partial lactone reduction to hydroxyaldehyde followed by Grignard addition, selective oxidation of the primary hydroxyl group, and Wittig reaction.